Aplicación De Un Modelo Basado En La Gestión Del Conocimiento Para Mejorar El Nivel De Aprovechamiento De Las Tic. Estudio De Caso En Una Pyme Mexicana - León-Moreno, Francisco Javier; Cadena-Badilla, Jesús Martín; Vega-Robles, Ramón Arturo (European Scientific Journal, ESJ, 2018)
A very dynamic environment and constant technological advances are surrounding small and medium-sized enterprises (SMEs) in their commercial activities. The business context is becoming increasingly complex, as there are continually numerous aspects related to the application of knowledge, both financial, legal, organizacional and technological. In relation to the application of information and communication technologies (ICT), SMEs need to acquire and apply knowledge correctly to obtain the best use of these technologies in their business processes. Taking this scenario into account, the objective of this paper is to present the case study on the application of a conceptual model based on knowledge management (KM) to improve the level of use of ICT in the business processes of mexican SMEs. The model was applied in an SME of the commercial sector. The results obtained are exposed, as well as the conclusions and future perspectives of the work developed.